EVALUASI PELAKSANAAN PRAKTIK KERJA LAPANGAN PADA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH BERBASIS GOAL ORIENTATION - Linda Indiyarti Putri (Universitas Wahid Hasyim Semarang, 2023)
This evaluation research aims to describe the implementation of the Field Work Practice (PKL) program in the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) at Wahid Hasyim University. This evaluation research uses a Goal Oriented Evaluation Model. By using a random sampling technique, the research subjects were obtained as many as 41 students and 17 lecturers and heads of study programs. Data were analyzed using descriptive quantitative analysis. Data collection techniques using questionnaires, observation, documentation. Based on this method, data is collected through the following steps 1). Identified on the job training objectives; 2) formulate indicators of achieving the goals that have been set; 3) formulate the data obtained with the indicators that have been formulated. The main objective is divided into objective sub-components, namely: objective program sub-component, attitude sub-component, achievement objective program sub-component. All indicators in the sub-components were analyzed and obtained an average value of 83.6%. This means that the implementation of the PKL program in the PGMI Unwahas Study Program is good and the goals are achieved.